Revised cytoarchitectonic mapping of the human premotor cortex identifies seven areas and refines the localisation of frontal eye fields - Sabine H. Ruland; Benjamin Sigl; Jeanette Stangier; Svenja Caspers; Sebastian Bludau; Hartmut Mohlberg; Peter Pieperhoff; Katrin Amunts (Communications Biology)
Abstract The premotor cortex is involved in a variety of motor and cognitive functions that often cannot be unambiguously linked to its microstructural correlates. We re-analysed the cytoarchitecture of this region in ten post mortem brains using an observer-independent mapping approach. Seven areas (6d1-6d3, 6v1-6v3, 6r1) were identified. Based on their cytoarchitectonic similarity, they were grouped into three dorsal (6d1-3) and four ventral (6v1-3, 6r1) premotor areas, supporting the concept of a functionally distinct dorsal and ventral premotor cortex. The superior frontal sulcus was identified as landmark for this separation. Comparison of the new maps with functional studies indicates that the frontal and inferior frontal eye fields are located within the premotor cortex, specifically in areas 6v1 and 6v2, not in the prefrontal cortex. Functional profiles of the areas were determined, serving as an initial basis for a more detailed characterisation of the individual areas. The new maps are publicly available to inform neuroimaging studies and aiding clinical applications such as targeting lesions or tumors and avoiding motor or cognitive impairments.